#### Answer

{-4}

#### Work Step by Step

8(y + 2) = 2(3y + 4)
Step 1 : Use distributive property
8.y + 8.2 = 2.3y + 2.4
simplify
8y + 16 = 6y + 8
Step 2 : Collect variable terms on one side and constants on the other side.
subtract 6y from both the sides
8y + 16 - 6y = 6y + 8 -6y
2y + 16 = 8
subtract 16 from both the sides
2y+ 16 - 16 = 8 -16
2y = -8
Divide both the sides by 2
$\frac{2y}{2}$ = $\frac{-8}{2}$
y = -4
Now we check the proposed solution, -4 , by replacing y with -4 in the original equation.
Step 1: the original equation 8(y + 2) = 2(3y + 4)
Step2: Substitute -4 for for
8(-4 + 2) = 2(3(-4) + 4)
Step 3: Multiply 3(-4) = -12
8(-4 + 2) = 2(-12 + 4)
Step 4: Solve
8(-2) = 2(-8)
Multiply 8(-2) = -16, 2(-8) = -16
-16 =-16
Since the check results in true statement, we conclude that the solution set of the given equation is {-4}